The efficacy of local corticosteroid injection in the treatment of trigger finger (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Trigger finger is a condition that causes triggering, snapping or locking on flexion of the involved digit. Treatment modalities are conservative (Non-steroidal anti-inflammatory drugs, splints or corticosteroid injections) or operative (percutaneous or open release of A1 pulley- the first annular pulley of the fibro-osseous sheath of the fingers situated at the level of the metacarpophalengeal joint). The aim of this study is to evaluate the efficacy of corticosteroid injection for trigger finger in adults.Material and Methods: Fifty patients with 54 trigger digits were treated by one or two injections of methylprednisolone acetate with 1% lignocaine. Patients were followed-up for a period of 6 months.Results: Symptoms and signs resolved in 79.63% of the injected digits. Local adverse reactions to steroid injection- pain at the injection site and steroid flare were self-limiting. There was no tendon rupture or post-injection infection.Conclusion: The study concludes that steroid injection is an effective first line treatment for trigger finger in most patients.Janaki Medical College Journal of Medical Sciences (2017) Vol. 5(2): 13-18